The Influence of Problem-Based Learning Methods on Learning Outcomes and Student Motivation in Science Subjects at SDN 4 Abuan - I Ketut Dedi Agung Susanto Putra; Ni Luh Putu Nita Miliana Indrayanti (KARMAPATI (Kumpulan Artikel Mahasiswa Pendidikan Teknik Informatika), 2023)
This research examined the impact of implementing the Problem-Based Learning (PBL) method on the learning outcomes and motivation of fourth-grade science students at SDN 4 Abuan. It employed a quasi-experimental design with 52 students from both the fourth and fifth grades. The fourth grade served as the experimental group, while the fifth grade acted as the control group. The independent variable was the application of the PBL method, while the dependent variables encompassed students' learning outcomes and motivation. Data collection involved descriptive tests for the cognitive domain and questionnaires to assess motivation and student responses. The data analysis revealed a significant difference in learning outcomes between students taught with the PBL method and those receiving conventional instruction. The PBL method yielded higher student learning outcomes. Furthermore, the students displayed a notably high level of motivation when using the PBL method, and their responses were generally positive towards the scientific-based PBL approach. In summary, the study demonstrated that the PBL method positively affected both learning outcomes and student motivation. This suggests that implementing the PBL method in the teaching of fourth-grade science at SDN 4 Abuan can be a valuable approach to enhance learning and boost student engagement.